Penentuan Tingkat Kerusakan Mesin Mobil Pada Bengkel AFUK Service Menggunakan Metode Weighted Product - M. Arif Fauzan (Universitas Methodist Indonesia, 2025)
Determining the priority level of car engine damage is an essential aspect in improving workshop service efficiency. AFUK Service Workshop often encounters difficulties in deciding which type of engine damage should be repaired first, as each damage type has different frequencies, severity levels, repair durations, and costs. This study aims to determine the priority level of car engine damage using the Weighted Product (WP) method. The four criteria used include damage frequency, severity level, repair duration, and repair cost, with respective weights of 0.5, 0.2, 0.2, and 0.1. The research data were obtained through direct interviews with mechanics at the AFUK Service Workshop. Based on the analysis using the WP method, the results produced an ordered priority of engine damage types that represent the most dominant issues to be addressed first. The implementation of the Weighted Product method helps the workshop determine repair priorities objectively and efficiently, thereby supporting better decision-making and improving service quality.